Risk Factors for Lag Screw Cut Out in Intertrochanteric Hip Fractures Treated with Dynamic Hip Screw (DHS) in a Tertiary Care Hospital: A Case-Control Study - Ali Shah, Faaiz; Naeemullah; Mian Javed Iqbal; Mian Amjad Ali (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To determine the risk factors for Lag Screw cut out in intertrochanteric hip fractures treated with Dynamic Hip Screw(DHS). METHODOLOGY: This case-control study was conducted in the orthopedic division of Lady Reading Hospital Peshawar. The medical records of all patients fulfilling the inclusion criteria and operated on between January 2019 and March 2024 were collected from the hospital’s Health Management Information System. All patients with DHS lag screw cut-outs were cases, while those without cut-outs were controls in a 1:1 ratio. Lag screw cut-out was tested for any association with other independent variables by calculating the Odds Ratio(OR), Confidence Interval(CI) and P-value. Multivariate analysis utilizing logistic regression was performed for all statistically significant independent variables (P<0.05) on univariate analysis. RESULTS: The data of 33 patients with lag screw cut out was compared with 33 patients without lag screw cut-outs. TAD more than 25 mm was associated with a 5-fold increased risk of cut-out (P=0.001, aOR=5.32,95% CI=2.10-3.32). Superior and lateral lag screw position was associated with 4-fold (P=0.02, aOR=4.33, 95% CI=4.51-7.62) and 3-fold (P=0.01, aOR=3.20, 95% CI=0.07-0.08) increased risk of lag screw cut-out respectively. Poor fracture reduction was associated with a 2-fold increased risk of lag screw cut-out (P=0.01, aOR=2.40, 95% CI=0.02-0.06). CONCLUSION: Increase Tip Apex Distance(TAD), superior and posterior lag screw position and poor fracture reduction were the independent risk factors significantly associated with lag screw cut-out in patients of intertrochanteric fractures treated with Dynamic Hip Screw(DHS).